ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN KONSUMEN PADA CV LANGEN RASA: - Muhammad Agil Ilyasa; Rahmi Widianti; Siti Mardah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
. Service quality is one of the key factors influencing customer satisfaction and business sustainability. CV Langen Rasa, a company engaged in the distribution of fresh vegetables to hotels and restaurants, must maintain excellent service quality to meet customer expectations amid increasing competition. This study aims to analyze the quality of service provided by CV Langen Rasa in improving customer satisfaction. The research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the owner, employees, and customers of CV Langen Rasa. The collected data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the quality of service at CV Langen Rasa has generally been implemented effectively through reliability in product delivery, responsiveness to customer requests and complaints, assurance of product quality, empathy toward customer needs, and adequate physical facilities. These service dimensions contribute positively to customer satisfaction by fostering trust, loyalty, and long-term business relationships. However, several challenges remain, including fluctuations in product availability due to weather conditions and limitations in human resources during peak demand periods. The study implies that continuous improvement in service quality, supported by effective communication, employee competency development, and service innovation, is essential to enhance customer satisfaction and strengthen the company's competitiveness in the hospitality supply industry. Keywords: competitiveness; customer satisfaction; CV Langen Rasa; service quality; qualitative research.